Hiking preparedness model (HiPrep): a scenario of Malaysian hikers awareness / Nik Jazwiri Johannis … [et al.] - Johannis, Nik Jazwiri; Mohd Yasim, Mazuki; Ariffin, Azli; Mohd Said, Omar Firdaus; Shafie, Mohd Shariman; A. Rahman, Muhammad Wafi; Mohd Sidi, M Adli (Universiti Teknologi MARA, 2020)
Mountain hiking is a well-known outdoor recreation activity in Malaysia. In fact, it became phenomenon since 2016 when the social media platform took place as a mainstream. Many people tend to hike some hiking spot which went viral. They liked to share their awesome pictures and experience as well. However, since then, accident and incident during mountain hiking activities in Malaysia drastically increased. Many hikers injured, died and lost in the jungle which previous study showed that human led were part of the cause. As a result, tons of SAR operations have been done and it was costly, time consumed and difficult. Regard to this circumstance, hiker’s preparedness doubted. Therefore, the main purpose of this study was to know the scenario of Malaysian hiker awareness on hiking preparedness from the expert point of view. Thus, an interview of local experts had been conducted. The finding showed, all the experts agreed that most of hikers nowadays were lack of knowledge about preparedness in terms of physical, knowledge and equipment. They stress out that most of the new hikers were not carried along basic things during their hiked such as headlamp, extra clothes, extra food and drinks, whistle and pocket knife. Experts also revealed that many newbie hikers didn’t wear appropriate attire during a hike such as wrong shoes and backpack which end up with safety issue. This results could make researchers in the same area of interest to aware on the hikers’ scenario in order to capture the Hiking Preparedness Model (HiPrep) in the future plans especially Hiking concerned.